Menerapkan Pendidikan Holistik dan Komprehensif untuk Meningkatkan Perkembangan Moral, Intelektual, dan Sosial Siswa - Lilis Sumiyati; Fadya Shofa Nada; Fahmi Lestari Prasetiadi; Abdul Aziz (Jurnal Budi Pekerti Agama Islam, 2025)
The rapid progress of technology, increasing globalization, and shifting socio-economic conditions pose major challenges for education in the digital age. This study investigates how holistic education fosters competencies aligned with future demands. Utilizing a qualitative method, it conducts a literature review with descriptive analytical techniques. Holistic education plays a crucial role in nurturing creativity, critical thinking, effective communication, and collaboration. It serves as a strategic response to global issues such as technological innovation and fast-paced societal transformations. Beyond equipping students to navigate digital challenges, holistic education also cultivates adaptability, leadership skills, and strong work ethics to handle unexpected changes. More than merely delivering academic content, holistic education aims to build character and prepare future generations to thrive as capable and competitive leaders.